PATTERN OF SOLID PAEDIATRIC MALIGNANT NEOPLASM AT LUMHS, JAMSHORO, PAKISTAN - Memon, Farzana; Rathi, Shankar Lal; Memon, Manzoor H. (Journal of Ayub Medical College Abbottabad, 2007)
Background: To evaluate pattern and frequency of solid malignant tumour in paediatric age group in our region. Methods: A retrospective study of 113 patients, whose surgical biopsies submitted in histopathology section of Pathology department, LUMHS Jamshoro from January 2001 to December 2005. Results: Total of 113 cases, 61 male and 52 female children in age group from 4 months to 15 years were diagnosed as solid malignant tumour with M/F ratio of 1.79:1 and mean age of 6.6 year. Maximum no. of patients was in 0-4 age 50.4%, followed by 32.7% in 4-9 and 16.8% in 10-15 years. The five most common tumours were Retinoblastoma 38.9%, Wilm's tumour 13.2%, Brain tumour (Glial tumours) 10.6%, Hodgkin disease 9.7% and soft tissue sarcomas 9.7%. Retinoblastoma and Wilm's tumour were common in 0-4 year age group, where as rest of tumour were more frequent in 5-9 and 10-15 years age group. Brain tumours and soft tissue sarcomas were common in females, while Hodgkin's disease was more common in males. Conclusion: Retinoblastoma was most common solid malignant tumour in early age group. It calls for ophthalmologic screening of all children below 1 year and high risk children until the age of 7 year, in order to detect retinoblastoma as early as possible. Keywords: Paediatric cancer; Retinoblastoma.